Assessments of sensory processing in infants and children with autism spectrum disorder between 0–12 years old: A scoping review. (April 2020) - Yeung, Lok Him Jason; Thomacos, Nikos
Highlights: A scoping review on the use of sensory assessments with infants and children with ASD from 0 to 12 years was undertaken. The Short Sensory Profile and Sensory Profile were the two most commonly used assessments. Among the four different ways of administering sensory assessments identified, most assessments were undertaken by carers. None of the identified assessments evaluate all modalities and domains hypothesised to be related to sensory processing. Incomplete psychometric data about some identified assessments means that drawing conclusions about them is difficult. Abstract: Background: Sensory processing has been increasingly researched, especially in respect to its association with Autism Spectrum Disorder (ASD). Children who experience ASD often also experience sensory processing difficulties, yet, a gap in the evidence remains regarding the use of sensory assessments specifically with infants and children with ASD aged 0–12 years. To address this gap and given that children in this age group typically move through three levels of education during these years, a scoping review was conducted. Method: The scoping review reviewed the peer-reviewed literature since 2008 in order to identify research that examined the use of sensory assessments with children with ASD aged 0–12. Seven databases were used. Results: Of the 37 articles included in this review, and 12 sensory assessments were identified. Three themes emerged: (a) administration, (b) focus and content, and, (c) reliability and validity. Conclusions: The findings suggest that additional research is necessary given the diversity in assessments and their application to the target population. Considering the available evidence, it is difficult to identify which is/are the most appropriate, psychometrically-sound assessment(s) when assessing sensory processing with this population. As assessments are administered in different ways; appear to capture slightly different sensory modalities and concepts related to sensory processing; and given that the psychometric properties of some assessments are poor to moderate, it is suggested that health professionals interpret sensory assessment findings with caution. It is also recommended that health professionals utilise a variety of sensory assessments.